Circularly Polarized Stack-Patch Microstrip Array Antenna for ETS-VIII Applications - Muhammad Fauzan Edy Purnomo (Fakultas Teknik, Universitas Brawijaya, 2009)
By using the H-IIA Launch Vehicle No. 11 from the Tanegashima Space Center, in the south of Kagoshima Prefecture Japan, ETS-VIII (Engineering Test Satellite VIII) has been launched successfully in the end of 2006. The ETS-VIII is one of the largest geostationary Sband satellites in the world to meet future requirements of voice and data communications, broadcasting and global positioning [1].Backward-looking, there are various types of antennas which developed aiming at ETS-VIII [2]-[5]. A part of the antennas [3] have been experimented outdoor by use of a pseudo-satellite station. Moreover, in order to obtain a good performance antenna to clarify suitably result on frequency characteristic, return loss, and radiation pattern, and also to obtain a simple configuration such as small, light and low profile, a left-handed circularly polarized stack-patch microstrip array antenna is proposed. The antenna was calculated by the Method of Moments using probe-fed pentagonal array antenna as radiating patch and triangular array antenna as parasitic patch with dielectric relative permittivity 2.17 and loss tangent 0.0009.In this paper, it discuss about the performances of antenna above at El=48° both of calculation and measurement results, the examined of performance beam antenna at low elevation, and the performances of antennas to take in signal from ETS-VIII satellites. The measured results at El=48° agree well with the calculated results of 5 dBic gain, and the 3-dB axial ratio beamwidth of the whole azimuth range about more of 120° for each beam coverage in the conical-cut direction satisfy for ETS-VIII applications.